2006
DOI: 10.1302/0301-620x.88b2.16274
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of acetabular dysplasia in cerebral palsy

Abstract: We carried out a morphometric analysis of acetabular dysplasia in patients with cerebral palsy requiring hip surgery using three-dimensional CT. We evaluated 54 hips in 27 patients. The contralateral normal hips of ten patients with unilateral Perthes' disease were used as a control group. The acetabular defects were assessed qualitatively as anterior, posterior or global. Quantitative assessments were made using three-directional acetabular indices (anterosuperior, superolateral and posterosuperior) and measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 14 publications
1
46
0
2
Order By: Relevance
“…6,9,13 We found that the volume was increased after Dega osteotomy. Previously, Ozgur et al 13 used the coronal image obtained on MRI to calculate acetabular volume in DDH.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…6,9,13 We found that the volume was increased after Dega osteotomy. Previously, Ozgur et al 13 used the coronal image obtained on MRI to calculate acetabular volume in DDH.…”
Section: Discussionmentioning
confidence: 74%
“…1). The acetabular volume was determined by integrating the acetabular area in the axial image and the slice thickness, 6 a method which has been verified by Slomczykowski et al 9 In order to establish the inter-and intra-observer reliability of the CT measurements, they were undertaken by two orthopaedic surgeons (CYC, MSP) and a chief resident. The orthopaedic surgeons had 20 and five years' experience, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of acetabular dysplasia has been known to correlate with the migration percentage of hip displacement [6,9,17]. With femoral deformities, imbalance of muscle forces and lack of ambulation lead to excessive anteversion and coxa valga that increase with the levels of gross motor function [31].…”
Section: Introductionmentioning
confidence: 99%